How Cloud Services may Enable SMEs to Overcome International Growth Challenges: Finnish SMEs in the IT Industry - Matero Párraga, Kaarlo (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Digitalization and technology megatrends such as Cloud services have provided SMEs with a suitable atmosphere and conditions to internationalize and seek for further business growth. There is a limited amount of research on Cloud services from the business perspective and the limitations and challenges SMEs encounter when pursuing international business growth. Thus, the main research question of this study was how Cloud services may enable Finnish SMEs to overcome international growth challenges. The research question was further divided into three sub-questions dealing with matters related to features and characteristics of Cloud services, limitations and challenges Finnish SMEs experience when pursuing international growth of business, and benefits and advantages of utilizing Cloud services to mitigate and suppress international growth challenges. First, the theoretical framework of this study was constructed based on the existing literature on Cloud services, SMEs, and international growth challenges. After this, qualitative research approach and methodology were applied for this study. The data was collected through six semi-structured expert interviews in person with representatives of IBM, Exidio, Big Data Solutions, and Comptel. After analyzing the collected data by applying thematic analysis method, the results were compared with the existing theory and the original framework was modified and complemented accordingly. Resource scarcity, customer base expansion and retention, and lack of courage to try new things and take risks turned out to be major international growth challenges of Finnish SMEs. Due to a number of benefits and advantages of utilizing Cloud services including service automation, consumption-based pricing model, lack of capital expenditures (capex) and huge upfront investments, lightened organization structure, cost savings, speed, accessibility, scalability, agility, geographical expansion potential, global reaching and covering, credibility, partners, enhanced CRM, freedom, and flexibility, it can be concluded that Cloud services can help directly and indirectly Finnish SMEs to mitigate and overcome international growth challenges and enable further business growth.